Protocol for research examination of individual suicides occurring in chronic pain: A qualitative approach to psychological autopsy methodology - Stefan G. Kertesz; Allyson L. Varley; April E. Hoge; Thomas E. Joiner; Beth D. Darnall; Kate M. Nicholson; Lera A. Fuqua; Mary F. Gilmore; Kevin R. Riggs; Stephanie A. Gamble; Adam J. Gordon; Yogesh Dwivedi; et al. (PLoS ONE, 2025)
Introduction In the United States, taper and discontinuation of opioids prescribed for long-term pain have emerged as statistical correlates of suicidal events. Suicide is a complex and multidetermined event reflecting a combination of risks occurring over time in a particular narrative context. Prevention of suicides should be informed by a detailed understanding of life events, pain-related and other risk factors contributing to these tragedies. To date, there have been no efforts to qualitatively profile these suicides through interview of bereaved survivors or review of medical records. This method is usually termed “psychological autopsy.”. Aims This paper summarizes the protocol for the Clinical Context of Suicide Following Opioid Transitions (CSI:OPIOIDs) study. The study seeks to qualitatively characterize patient and clinical context factors associated with suicide among persons who died by suicide in the context of opioid stoppage or reduction, and to compare findings between Veteran and non-Veteran decedents. Methods In the United States, there is no master list for suicide deaths linked to an antemortem health care event. For this reason, recruitment requires public advertising followed by screening of bereaved individuals who wish to participate. Data collection and interpretation are guided by the Social-Ecological Model for suicide. The study involves a collaboration of persons with lived experience and disciplinary experts in suicide, primary care, pain, health services, and medical anthropology. Conclusions This study aims to deliver the first in-depth analysis of suicide events occurring in persons with chronic pain who died by suicide in the context of a prescription opioid reduction or stoppage. The results should provide insights that can guide alterations to care by health systems and by individual practitioners.